The Relationship Between Pregnant Women's Knowledge About Anemia and Stunting - Rosiana, Agnes; Angela, Monica (Cattleya Darmaya Fortuna, 2022)
This research aims to investigate the association between pregnant women's knowledge regarding anemia and the prevalence of stunting among toddlers in Mandailing Natal district, where stunting rates exceed the provincial average of 25.8% in North Sumatra Province. Utilizing an analytical survey method with a cross-sectional approach, the study population consisted of 40 pregnant women attending the Longat Community Health Center, with total sampling employed as the sampling technique. Data collection involved the use of questionnaires, and analysis was conducted using the chi-square test with a significance level set at p<0.05. The analysis revealed that a majority of pregnant women possessed adequate knowledge regarding anemia and stunting, comprising 21 individuals (52.5%). Statistical tests further indicated a significant relationship between pregnant women's knowledge concerning anemia and the incidence of stunting, particularly based on factors such as age (p=0.046), education (p=0.001), economic status (p=0.013), information sources (p=0.013), and parity (p=0.030). It is recommended that healthcare professionals engage in outreach and counseling initiatives to enhance pregnant women's awareness regarding the repercussions of anemia on both fetal and maternal health.